ANALISA HANDLING BARANG EKSPOR PADA PT BHANDA GHARA REKSA (Persero) - Musdirwan Musdirwan; Kiki Silvi Monika (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2019)
PT. Bhanda Ghara Reksa is a company engaged in warehousing service. PT.BGR is providing, renting out, and managing warehouse space, both close and open (Open Storage). PT. Perkebunan Nusantara VIII Bandung in collaboration with the BGR in handling goods export activities using Term FOB (Free On Board). In this case, the author analyzes how the procedure for handling exports carried out by PT. BGR using FOB (Free on Board) and also analyzes how much the cost incurred for one-time shipment of export commodities of tea commodities with the term Free On Board (FOB) of PT.Bhanda Ghara Reksa (Persero) in the framework of security system to the consumer's hands. And whether from the existing analysis of the customer, PT. Perkebunan Nusantara VIII Bandung has subjected to financing appropriate for the correct calculation amount corresponding agreement with the delivery of Free On Board (FOB). Through a calculation result obtained from Free On Board (FOB) in the amount of Rp. 1,048.44 / kg or the fee charged to the exporter Rp. 1,048.44 x 26,400 kg = Rp. 27,678,816,- to PT.Perkebunan Nusantara VIII Bandung.